Variations in clutch size and breeding success of Greylag Geese Anser anser in the Uists, Scotland - Paterson, I W; Boyer, P R; Massen, D D (Wildfowl, 1990)
The native Greylag Goose population on the Uists, Scotland, has doubled since the 1960s and the principal breeding areas moved from South to North Uist. Comparisons of clutch and brood sizes found that both were significantly smaller on North Uist. Clutch sizes were not significantly smaller on South Uist than at Loch Druidibeg, South Uist, in 1968-72. The smaller clutch sizes and broods on North Uist were not due to differences in nesting habitat, predation rates, food quality, or differences in laying dates between North and South Uist. The differences may be attributable to young birds laying smaller clutches on North Uist due to changes in the age structure of the Uist population as it expanded.